Toxicological assessment of sediment samples from the protected Kerekudvar section of the Zagyva River using classic and alternative fish models - Bock, Illés; Csorbai, Balázs; Bokor, Zoltán; Garai, Edina; Vásárhelyi, Erna; Kerekes, Flóra; Urbányi, Béla; Csenki-Bakos, Katalin; Csenki-Bakos, Zsolt (Animal welfare, Ethology and Housing Systems (AWETH), 2020)
In the course of our research, we tested sediment samples from the protected Kerekudvar section of the Zagyva River at three sampling points on different fish models. Our experiments were performed in the model organism zebrafish (Danio rerio) and in two species naturally found in the given river section, the orfe (Leuciscus idus) and the chub (Squalius cephalus). Two different embryo toxicity tests were performed, a sediment contact assay and an acute toxicity test with organic extract from sediment samples. The orfe embryos showed 100% mortality even at the lowest test concentration during the sediment contact assay, so this species cannot be used in this type of test. For zebrafish and chub, significant differences were observed at all three sampling points and at all but the lowest test concentrations. In the case of the organic extract test, the orfe embryos showed the highest mortality again, while in the case of the other two species, the mortality did not reach 50% at any of the test concentrations. Because we found significant differences between the results of the laboratory model and the alternative models for both tests used, we concluded that it is recommended to consider the inclusion of alternative model species in sediment toxicology surveys.